2017
DOI: 10.1002/ppap.201600256
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Ag/a-C:H nanocomposite films with Ag surface enrichment

Abstract: The nanocomposite films Ag/a‐C:H were prepared by vacuum‐based method which combines deposition of Ag nanoparticles by means of gas aggregation source (GAS) and PECVD deposition of a‐C:H matrix. The matrix was deposited in a mixture of Ar and n‐hexane on the substrates placed on the powered RF electrode facing the beam of Ag NPs from the GAS. Anisotropic plasma etching was used to increase Ag concentration on the surface of the coating. The influence of three types of plasma on the chemical composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It has recently been shown that the deposition of metal NPs using the cluster beam technique is an efficient approach in the formation of polymer composite films with antibacterial properties. The composites can be formed by either incorporation of particles formed in a cluster source into polymer simultaneously synthesized by plasma-enhanced chemical vapour deposition, by coating the NPs with a thin overlay or by soft landing of clusters on ex situ fabricated films followed by thermal annealing facilitating the partial embedding of clusters into the polymer [ 9 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the deposition of metal NPs using the cluster beam technique is an efficient approach in the formation of polymer composite films with antibacterial properties. The composites can be formed by either incorporation of particles formed in a cluster source into polymer simultaneously synthesized by plasma-enhanced chemical vapour deposition, by coating the NPs with a thin overlay or by soft landing of clusters on ex situ fabricated films followed by thermal annealing facilitating the partial embedding of clusters into the polymer [ 9 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A vacuum setup was constructed that combined a gas aggregation cluster source (GAS) for the production of nanoparticles (NPs) and a main deposition chamber where thin films were deposited by plasma enhanced chemical vapor deposition (PECVD) similarly as reported in our recent work (see also Scheme S1) …”
Section: Methodsmentioning
confidence: 99%
“…Another strategy that makes it possible to completely decouple the deposition of Ag NPs and the plasma polymer matrix is based on the use of gas aggregation sources [ 134 , 135 ]. This approach was recently used by Vaidulych et al [ 133 ] for the deposition of Ag/a-C:H nanocomposites. In order to produce hard coatings, the substrates were placed on a RF electrode, used for a-C:H matrix deposition, perpendicularly to the direction of a beam of Ag NPs produced by the GAS system ( Figure 4 c).…”
Section: Antibacterial Ag/plasma Polymer Nanocompositesmentioning
confidence: 99%
“…As it was shown in a previous study focusing on Cu/a-C:H nanocomposites [ 136 ], the volume fraction of metallic NPs in a-C:H matrix and connected antibacterial efficiency may be tuned either by the current applied onto the DC magnetron in the gas aggregation source, or by changing the duty cycle of RF power used for the matrix deposition. Furthermore, it was reported that antibacterial action of Ag/a-C:H coatings may be enhanced by the partial etching of nanocomposites by plasma treatment performed in the same deposition chamber resulting in partial removal of a carbonaceous layer from the outermost surface of produced nanocomposites, thus making Ag NPs more accessible for water [ 133 ].…”
Section: Antibacterial Ag/plasma Polymer Nanocompositesmentioning
confidence: 99%